Latent profile analysis of sense of coherence and relationship with meaning of life and professional identity among nursing undergraduate - Yating Liu; Dudu Zhang; Song Ge; Shanshan Wang; Xin Li; Zhenxiang Zhang; Beilei Lin; Suyan Chen; Yongxia Mei (BMC Nursing)
Abstract Background Enhancing nursing undergraduates’ sense of coherence is crucial for the growth of the nursing workforce. Yet, existing research primarily examines the aggregate level of sense of coherence among nursing undergraduates and its correlations with other variables, overlooking the individual heterogeneity in nursing undergraduates’ sense of coherence in nursing. This study aimed to identify different subgroups of nursing undergraduates’ sense of coherence and explore the influencing factors pertinent to each subgroup. Methods A cross-sectional study was conducted from May to June 2020 among 1,251 nursing undergraduates using convenience sampling. Latent profile analysis was employed to identify subgroups of nursing undergraduates’ sense of coherence, and multiple logistic regression was utilized to analyze the factors associated with each subgroup. Results Four potential subtypes of nursing undergraduates’ sense of coherence were identified: low sensitivity-low coping group (25.7%), high sensitivity-high coping group (29.7%), moderate sensitivity-moderate coping group (17.8%), and high sensitivity-low coping group (26.8%). Multiple logistic regression analysis revealed that factors influencing nursing undergraduates’ sense of coherence included family financial situation, high school subject choice, religious beliefs, belief in having good interpersonal relationships, meaning in life, and professional identity. Conclusion The heterogeneity of nursing undergraduates’ sense of coherence suggests that nursing educators should provide targeted intervention guidance according to the potential category characteristics of nursing undergraduates’ sense of coherence; at the same time, they should strengthen the cultivation of nursing undergraduates’ meaning of life and professional identity to improve their level of sense of coherence, so as to promote the growth of the nursing workforce.